Effects of selenization time and temperature on the growth of Cu2ZnSnSe4 thin films on a metal substrate for flexible solar cells. (15th January 2019) - Stanchik, A.V.; Gremenok, V.F.; Juskenas, R.; Tyukhov, I.I.; Tivanov, M.S.; Fettkenhauer, Ch.; Shvartsman, V.V.; Giraitis, R.; Hagemann, U.; Lupascu, D.C.
Highlights: The CZTSe thin films were fabricated by selenization of electrodeposited precursors. The influence of selenization conditions on physical properties of films was studied. The CZTSe films were characterized by SEM/EDX, XRD, TOF-SIMS and optical spectroscopy. Optimal conditions for precursors selenization are temperature 560 °C and time 30 min. Abstract: Thin film Cu2 ZnSnSe4 (CZTSe) solar cells can be grown on flexible and lightweight metal substrates allowing their direct integration on bendable surfaces and where the weight of solar cell is an important criterion. Flexible substrates make it possible to use the roll-to-roll technology of solar cells, which leads to an additional reduction in the cost of production and final cost of solar cells. The CZTSe thin films were fabricated by selenization of electrodeposited metallic precursors onto tantalum (Ta) flexible substrates at different temperature and time. The results of the effect of selenization temperature and time on the morphology, structural, and optical property of the CZTSe films are presented in this work. It was found that the morphology of the CZTSe thin films depend on their elemental composition and time of selenization. Experimental data indicate that composition of the CZTSe films selenized within 10 and 20 min at 560 °C have the CZTSe basic phase and secondary phases (CuSe, SnSe and ZnSe). In contrast, the increase in selenization temperature and/or time leads to disappearing of the secondary phases (CuSe, SnSe) and better crystallization of the CZTSe films. It was found that films selenized at 560 and 580 °C within the same time have similar characteristics. Depending on selenization time and temperature of the CZTSe, thin films exhibited a shift in band gap from 1.16 to 1.19 and to 1.22 eV, respectively. The change of band gap of the CZTSe thin films is associated with changes of elemental and phase compositions, and thickness of the film. These results showed that the received CZTSe films on Ta foil can be used for fabrication of thin film solar cells.